Association between adult body shape index and serum levels of the anti-aging protein Klotho in adults: a population-based cross-sectional study of the NHANES from 2007 to 2016 - Gong, Li; Xu, Jinghan; Zhuang, Yiyang; Zeng, Liwei; Peng, Zhenfei; Liu, Yuzhou; Huang, Yinluan; Chen, Yutian; Huang, Fengyi; Piao, Chunli (Frontiers in Endocrinology, 2025)
PurposeAdult body shape index (ABSI) is widely recognized as a reliable indicator for evaluating body fat distribution and dysfunction. However, the relationship between ABSI and Klotho protein, known for its anti-aging biological function, has not yet been investigated. Therefore, the aim of this study was to assess the correlation between ABSI and serum Klotho levels in adults residing in the United States.MethodsA cross-sectional study of participants was conducted based on the 2007–2016 National Health and Nutrition Examination Survey. Visceral adiposity was determined using the ABSI score, and Klotho protein concentration was measured using an enzyme-linked immunosorbent assay kit. Multiple regression models were used to estimate the association between ABSI and Klotho protein after adjusting for several potential confounding variables. Subgroup analysis of ABSI and Klotho was performed using restricted cubic splines.ResultA total of 11,070 adults were eligible for participation, with a mean ABSI of 8.28 ± 0.45 and a mean Klotho protein concentration of 853.33 ± 309.80 pg/mL. Multivariate regression analysis showed that participants with high ABSI scores had lower serum Klotho protein concentrations. When ABSI was divided into quartiles, after full adjustment, Klotho protein levels were lower in participants in the fourth fully adjusted ABSI quartile (Q4: -0.352 pg/ml) than in those in the lowest quartile (Q1) (P<0.0001).ConclusionThere was a negative linear correlation between ABSI score and serum Klotho concentration. Higher ABSI was associated with lower serum Klotho concentrations; however, this association did not seem to be significant in subjects with BMI ≥30 kg/m2.Further study is needed to verify the causality of this association and elucidate the underlying mechanisms.